Printed Agitation Materials as a Factor in Soviet Migration in the Late 1940s–1950s (Case Study of Molotov Oblast) - Glushkov, Alexander V.; Kozlova, Kristina O. (The New Research of Tuva, 2025)
This article examines printed agitation materials used by Soviet authorities during voluntary resettlement campaigns of the postwar period (late 1940s–1950s) to support various sectors of industry in the Urals and the eastern regions of the USSR. In the postwar years, the Urals, Siberia, and the Far East became macro-regions with a high proportion of incoming population. The present study focuses on one of the Ural regions — Molotov Oblast.The most common forms of agitation disseminated in “donor regions” were printed brochures describing the advantages of relocating to specific areas. Agitation work, however, continued with those settlers who had already arrived on site. As a rule, to secure workforce retention, permanent agitation columns were maintained in the pages of mass-circulation publications of organizations and enterprises. Thus, in the first case, agitation can be viewed as a “pull” factor, whereas in the second, it served as a means of counteracting return migration (“reverse movement”).In the Urals, a large inflow of labor from the central RSFSR and the Byelorussian SSR was observed in Molotov Oblast (renamed Perm Oblast in 1957). The region required personnel for the forestry industry, factories, and major construction projects. Resettlement was accompanied by extensive ideological work — initially in labor “donor regions” and subsequently directly in the settlement areas. First, agitation brochures were used to create a favorable image of the recipient region; then, periodicals employed various methods to influence settlers, motivating them to remain. Mass-circulation publications shaped a positive image of the settler, portraying the overcoming of present hardships and promising a prosperous future conditional on dedicated labor.The analysis undertaken in this study enabled the authors to trace the evolution of Soviet agitation in the first postwar decade, to identify the main agitation techniques — marked by considerable variety — and to conclude that at the turn of the 1940s–1950s, under the conditions of voluntary resettlement campaigns, the state was compelled to seek new methods of influencing potential migrants.
Keywords: history of the USSR; postwar period; Urals; Siberia; labor migration; settler; agitation; propaganda